Life-threatening and major cardiac events during long-distance races: updates from the prospective RACE PARIS registry with a systematic review and meta-analysis. (27th July 2020) - Gerardin, Benoît; Guedeney, Paul; Bellemain-Appaix, Anne; Levasseur, Thomas; Mustafic, Hazrije; Benamer, Hakim; Monsegu, Jacques; Lamhaut, Lionel; Montalescot, Gilles; Aubry, Pierre; Collet, Jean-Philippe; ,
Abstract: Aims: Limited data exist regarding the incidence and aetiology of life-threatening events such as major cardiac events or exertional heat stroke during long-distance races. We aimed to provide an updated incidence, etiology and prognosis of life-threatening events during long-distance races. Methods: The prospective RACE PARIS registry recorded all life-threatening events/fatal events occurring during 46 marathons, half-marathons and other long-distance races in the Paris area between 2006 and 2016, comprising 1, 073, 722 runners. Event characteristics were determined by review of medical records and interviews with survivors. Results: The incidence of life-threatening events, exertional heat stroke and major cardiac events was 3.35 per 100, 000, 1.02 per 100, 000 and 2.33 per 100, 000, respectively, including 18 sudden cardiac arrests (1.67 per 100, 000). The main aetiology of sudden cardiac arrest was myocardial ischaemia (11/18), due to acute coronary thrombosis (6/11), stable atherosclerotic coronary artery disease (2/11), coronary dissection (1/11), anomalous connection (1/11) or myocardial bridging (1/11). A third of participants with ischaemia-related major cardiac events presented with pre-race clinical symptoms. Major cardiac events were more frequent in the case of a high pollution index (6.78 per 100, 000 vs. 2.07 per 100, 000, odds ratio 3.27, 95% confidence interval 1.12–9.54). Case fatality was low (0.19 per 100, 000). Similarly, we report in a meta-analysis of eight long-distance race registries comprising 16, 223, 866 runners a low incidence of long-distance race-related sudden cardiac arrest (0.82 per 100, 000) and fatality (0.39 per 100, 000). Death following sudden cardiac arrest was strongly associated with initial asystole or pulseless rhythm. Conclusion: Long-distance race-related life-threatening events remain rare although serious events. Better information for runners on the risk of pre-race clinical symptoms, outside air pollution and temperature may reduce their incidence.